Ultrasensitive PbS‐Quantum‐Dot Photodetectors for Visible–Near‐Infrared Light Through Surface Atomic‐Ligand Exchange. (9th November 2015) - Mi, Longfei; Yu, Yongqiang; Wang, Hui; Zhang, Yan; Yao, Xudong; Chang, Yajing; Wang, Xiaoming; Jiang, Yang
Abstract : A surface atomic‐ligand exchange method is applied the first time in the construction of photodetectors (PDs) based on PbS quantum dots (QDs) for ultrasensitivity. The device thus produces a high photosensitivity to visible and near‐infrared light with a photoresponsivity up to 7.5 × 10 3 A W −1 and a high stability in air. In particular, these PbS‐QD‐based PDs show the capability of following a pulse light with a frequency up to 100 kHz well at a relatively fast response time/recovery time of ≈4/40 μs, much faster than most previous QD‐based PDs. The short response time is attributed to modification for the surface of the PbS‐QDs by cetyltrimethylammonium bromide treatment, which effectively improves the contact between the QDs and the Au electrodes, leading to extracting a high carrier mobility (≈0.142 cm 2 V −1 s −1 ). These findings show the great potential of PbS‐QDs as high‐speed nano‐photodetectors, and, more importantly, demonstrate the importance of the surface atomic‐ligand exchange method in the construction of QD‐based devices. Abstract : Photodetectors based on PbS quantum dots are first constructed by using an atomic‐ligand exchange method. They yield high device performances, i.e., responsivity up to 7.5 × 10 3 A W −1, relatively fast response time/recovery time of ≈4/40 μs and higher stability to 100 kHz pulsed light.